Novel method to detect microRNAs using chip-based QuantStudio 3D digital PCR. (December 2015) - Conte, Davide; Verri, Carla; Borzi, Cristina; Suatoni, Paola; Pastorino, Ugo; Sozzi, Gabriella; Fortunato, Orazio
Abstract Background Research efforts for the management of cancer, in particular for lung cancer, are directed to identify new strategies for its early detection. MicroRNAs (miRNAs) are a new promising class of circulating biomarkers for cancer detection, but lack of consensus on data normalization methods has affected the diagnostic potential of circulating miRNAs. There is a growing interest in techniques that allow an absolute quantification of miRNAs which could be useful for early diagnosis. Recently, digital PCR, mainly based on droplets generation, emerged as an affordable technology for precise and absolute quantification of nucleic acids. Results In this work, we described a new interesting approach for profiling circulating miRNAs in plasma samples using a chip-based platform, the QuantStudio 3D digital PCR. The proposed method was validated using synthethic oligonucleotide at serial dilutions in plasma samples of lung cancer patients and in lung tissues and cell lines. Conclusion Given its reproducibility and reliability, our approach could be potentially applied for the identification and quantification of miRNAs in other biological samples such as circulating exosomes or protein complexes. As chip-digital PCR becomes more established, it would be a robust tool for quantitative assessment of miRNA copy number for diagnosis of lung cancer and other diseases.